EFEKTIVITAS PERAN KEPEMIMPINAN KEPALA SEKOLAH MELALUI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN PROFESIONALISME GURU DI SD NEGERI 1 LAMBHEU KABUPATEN ACEH BESAR - Wina Widiana; Mislinawati; Aida Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The quality of learning in schools is strongly influenced by teachers’ professionalism, particularly pedagogical competence in planning, implementing, and evaluating the learning process. The improvement of teachers’ professionalism is closely related to the leadership role of the principal through the implementation of School-Based Management (SBM). This study aims to describe the effectiveness of the principal’s leadership role through managerial functions in SBM, which include planning, organizing, actuating, and controlling, in improving teachers’ professionalism at SD Negeri 1 Lambheu, Aceh Besar Regency. This study employed a qualitative approach with a descriptive method. Data were collected through observation and interviews with the principal and teachers. Data analysis used the model of Miles, Huberman, and Saldana, which includes data reduction, data display, and conclusion drawing. The results show that: (1) the planning function is carried out in a participatory manner by involving teachers in preparing work programs and learning tools; (2) the organizing function is implemented through the division of tasks according to teachers’ competencies and the management of learning facilities; (3) the actuating function is conducted through motivation, guidance, and strengthening collaboration among teachers; and (4) the controlling function is carried out through classroom supervision and evaluation of teachers’ performance. The implementation of the principal’s managerial functions through SBM contributes to improving teachers’ pedagogical professionalism. In general, the findings indicate that the principal’s leadership, implemented through systematic and continuous managerial functions within the framework of School-Based Management, is effective in enhancing teachers’ professionalism.